Pemahaman Investor Terhadap Shariah Online Trading System (SOTS) - Salsabila, Salsabila; Fithriady, Fithriady; Desiana, Rina (Disclosure: Journal of Accounting and Finance, 2023)
Investing is one of the most prominent activities in Islam. But before investing, every potential investor should have a sufficient understanding of the world of investment. This research was carried out to know the level of understanding of students of Shariah Online Trading System (SOTS) as well as to learn the steps taken by the Shariah Investment Gallery in giving the right understanding to investors. The method used is the mixed method (Quantitative - Qualitative). The results of research using quantitative methods showed that the level of understanding of investment students investors related to the mechanism of stock trading using SOTS belonged to the low category of 54.5%. Further reinforced by the results of the qualitative data analysis that also obtained that investor understanding is categorized in the level of translated understanding which is the lowest level of understanding. The steps taken by all managers of the Sharia Investment Gallery in providing the right understanding to investors is through activities such as socialization, education, as well as discussion.